Invasive aspergillosis complicated in a patient with non-small cell lung cancer harboring RET fusion during treatment with RET-TKIs: a case report and literature review - Kaidiriye Setiwalidi; Yimeng Li; Yuyan Ma; Zhanpeng Hao; Yujia Zhao; Yuxin Zhang; Xuan Liang; Tao Tian; Zhiping Ruan; Yu Yao; Xiao Fu (Frontiers in Oncology)
Pralsetinib and selpercatinib have been approved as specific tyrosine kinase inhibitors (TKIs) for the treatment of patients with non-small cell lung cancer (NSCLC) harboring rearranged during transfection (RET) fusion and mutation. However, adverse events associated with pralsetinib and selpercatinib are not fully understood, especially in the real world. In this case, invasive aspergillosis that appeared concurrent with RET-TKI targeted therapy is proposed to be an additional adverse drug reaction (ADR) that was not mentioned in previous reports. Here, we describe the process of clinical diagnosis and treatment of invasive aspergillosis and attempt to explore its possible pathogenesis in association with RET-TKI targeted therapy, with the aim of providing clinicians a more in-depth understanding of the ADR associated with RET-TKIs, as well as to prevent serious outcomes caused by reduction or discontinuation of antitumor therapy.